2009
DOI: 10.1007/s00484-009-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation induces early flowering: evidence from Platanus acerifolia and Prunus cerasus

Abstract: The effect of towns on plant phenology, i.e. advancement of spring development compared with a rural environment, via the urban heat island (UHI) phenomenon, has been shown for many towns in many countries. This work combines experimental and observational methodology to provide a better and deeper view of climatic habitat in an urban context with a view to understanding the relationship between plant development and urban climate on the intra-urban scale (by taking into account town structure). A dense networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 34 publications
11
93
1
3
Order By: Relevance
“…Therefore, we also found slightly stronger correlations with mean nighttime temperature than with mean temperature (exception > 50% leaves unfolded) and no statistically significant correlation with maximum temperature. This is in accordance with Wielgolaski (1999) and Mimet et al (2009) 38 37 37 37 37 37 37 ui, urban index; T m , mean temperature; T night , mean nighttime temperature; T max , maximum temperature; DTR, diurnal temperature range; RH, relative humidity; a, absolute humidity, in March (=3), August (=8) and September (=9); BBCH 61, beginning of flowering; BBCH 65, full flowering; BBCH 10, mouse-ear stage; BBCH 15, >50% of leaves unfolded; n, number of sites; P , significance, bold values: significant coefficients at the 5% level; bold and italic values: significant coefficients at the 10% level.…”
Section: Air Temperature Humidity and The Phenology Of Trees In Urbasupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we also found slightly stronger correlations with mean nighttime temperature than with mean temperature (exception > 50% leaves unfolded) and no statistically significant correlation with maximum temperature. This is in accordance with Wielgolaski (1999) and Mimet et al (2009) 38 37 37 37 37 37 37 ui, urban index; T m , mean temperature; T night , mean nighttime temperature; T max , maximum temperature; DTR, diurnal temperature range; RH, relative humidity; a, absolute humidity, in March (=3), August (=8) and September (=9); BBCH 61, beginning of flowering; BBCH 65, full flowering; BBCH 10, mouse-ear stage; BBCH 15, >50% of leaves unfolded; n, number of sites; P , significance, bold values: significant coefficients at the 5% level; bold and italic values: significant coefficients at the 10% level.…”
Section: Air Temperature Humidity and The Phenology Of Trees In Urbasupporting
confidence: 90%
“…The fact that UHI is greater for minimum than for maximum temperatures is well documented in existing literature (Landsberg, 1981;Baker et al, 2002;Mimet et al, 2009;Shustack et al, 2009), and was also shown in our study of Campinas and Munich. Furthermore, relative and absolute humidity were significantly lower in urban than rural Munich (−5.8% and −0.1 g m −3 , respectively).…”
Section: Uhi Effectsupporting
confidence: 89%
See 1 more Smart Citation
“…Platanus × acerifolia is very tolerant to numerous abiotic stresses such as limited root space, unfavourable soil conditions, drought, air pollution, urban climate (Mimet et al 2009) and exhibits high accumulation capacity of heavy metals (Ivanová et al 2007, Kang et al 2016 (Pilotti et al 2014). Considering the prevalence of plane trees in urban areas all over the world it is important to develop suitable measures to prevent or restrict the pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study is to present data about plant growth monitoring of these plant species cultivated in three different mixture of agronomic soil and decontaminated river sediments and analyze the relationship with air temperature and soil type. Several studies assessed that air temperature is the main meteo-climatic driver of plant phenology [3], [4] and plant growth [5] also in an urban environment due to the increase of urbanization [6], [7]. Several simulation models for plant phenology and plant growth are based on the so called GDD.…”
Section: Introductionmentioning
confidence: 99%